How Proficient are Class V Students in Language? - Kumar, Santosh; Agarwal, Mamta; Sharma, Manika (INDIAN EDUCATIONAL REVIEW, 2013)
National Council of Educational Research and Training conducted the National Achievement Survey at Class V in the year 2010 to find out the achievement level of students in different subjects (Language, Mathematics and Environmental Studies). In this paper the achievement of students in language especially in reading comprehension has been presented. The tests used for measuring the achievement consisted of three booklets containing different kinds of reading texts with multiple choice items on each text. The items were spread across the whole range of cognitive processes involved in reading comprehension. The responses of students to the various items were analysed using Item Response Theory. The paper shows how the Class V students performed on the reading comprehension items of various different levels and testing various reading abilities. It was found that Class V students in India are at different levels of language proficiency and that the teachers need to work on developing the competence of their students in reading different varieties of texts.